Barriers and Facilitators to Integrating Health Service Responses to Intimate Partner Violence in Low‐ and Middle‐Income Countries: A Comparative Health Systems and Service Analysis. Issue 2 (19th April 2017) - Colombini, Manuela; Dockerty, Colleen; Mayhew, Susannah H.
Abstract : This systematic review synthesizes 11 studies of health‐sector responses to intimate partner violence (IPV) in low‐ and middle‐income countries. The services that were most comprehensive and integrated in their responsiveness to IPV were primarily in primary health and antenatal care settings. Findings suggest that the following facilitators are important: availability of clear guidelines, policies, or protocols; management support; intersectoral coordination with clear, accessible on‐site and off‐site referral options; adequate and trained staff with accepting and empathetic attitudes toward survivors of IPV; initial and ongoing training for health workers; and a supportive and supervised environment in which to enact new IPV protocols. A key characteristic of the most integrated responses was the connection or "linkages" between different individual factors. Irrespective of their service entry point, what emerged as crucial was a connected systems‐level response, with all elements implemented in a coordinated manner.